2011
DOI: 10.1210/jc.2011-0114
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutations of the TMEM127 Gene in Patients with Paraganglioma of Head and Neck and Extraadrenal Abdominal Sites

Abstract: TMEM127 germline mutations confer risks of extraadrenal paraganglial tumors in addition to the documented adrenal pheochromocytoma. Thus, surveillance for extraadrenal and adrenal paraganglial tumors is likely warranted in TMEM127 mutation carriers, although the true prevalence should be evaluated in patients with extraadrenal paraganglial tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 11 publications
2
99
0
1
Order By: Relevance
“…Another study revealed one additional PCC patient with a TMEM127 mutation . No TMEM127 mutations were detected in 129 sympathetic and 60 parasympathetic PGLs (Yao et al 2010b), but in a recent study, germline missense variants were detected in two out of 48 patients with multiple PGLs (Neumann et al 2011), one of which also displayed bilateral PCC. Summarizing the 23 reported patients, all but one (96%) had PCC and 39% had bilateral PCC (Table 1).…”
Section: Tmem127-associated Pccs and Pglsmentioning
confidence: 92%
“…Another study revealed one additional PCC patient with a TMEM127 mutation . No TMEM127 mutations were detected in 129 sympathetic and 60 parasympathetic PGLs (Yao et al 2010b), but in a recent study, germline missense variants were detected in two out of 48 patients with multiple PGLs (Neumann et al 2011), one of which also displayed bilateral PCC. Summarizing the 23 reported patients, all but one (96%) had PCC and 39% had bilateral PCC (Table 1).…”
Section: Tmem127-associated Pccs and Pglsmentioning
confidence: 92%
“…Through both germline and somatic tumor testing of individuals with PGL, the prevalence of germline susceptibility genes altered in HNPGL is now ~30 to 40%, involving predominantly genes encoding subunits of succinate dehydrogenase ("SDHx" genes) [3,5]. In addition to SDHx, VHL, NF1 and RET, genes including MAX [6], TMEM127 [7] fumarate hydratase [8] and HIF2A [9] have now been associated with HNPGL in rare cases. The clinical implications of hereditary disease have led the Endocrine Society to recommend referring all patients diagnosed with PGL for clinical genetic testing regardless of site of origin or lack of familial events [10].…”
Section: Geneticsmentioning
confidence: 99%
“…The typical presentation is a unilateral adrenal pheo in patients with no prior family history. Recently, however, bilateral pheo, extraadrenal pgl, and hnpgl have been described 27,28 . The penetrance is unknown.…”
Section: Genetics Of Pheo-pgl: Non-syndromic Causesmentioning
confidence: 99%